Owens-Illinois Glass Block Building (R.R. Donnelley & Sons Co.)
This is the first full-sized structure built of glass block, recently perfected by the Owens-Illinois Glass Company, Toledo, Ohio. One hundred feet long and sixty feet wide with a gloriously colorful tower fifty-feet high, it is a wonderful spectacle by day and a magnificent display by night when interior lighting glows through its many-colored walls and tower. The Owens-Illinois Glass Company is one of the world's largest producers of glass containers and other glass products, which form one of the interesting exhibits inside the building